Characterizations of $δ p(Λ,s)$-$R_0$ Spaces (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concept of $δ p(Λ,s)$-$R_0$ spaces. Moreover, somecharacterizations of $δ p(Λ,s)$-$R_0$ spaces are investigated.
Keywords: $δ p(Λ,s)$-open set; $δ p(Λ,s)$-$R_0$ space